ANALISIS POTENSI EKONOMI DI SEKTOR DAN SUBSEKTOR PERTANIAN, KEHUTANAN DAN PERIKANAN KABUPATEN JEMBER - Rizani, Ahmad (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2017)
This study aims to examine the economic potential in the sector and sub-sector of agriculture, forestry and fishery of Jember Regency. In addition, this study also identifies and determines the leading sectors and sub-sectors in Jember Regency to provide an overview of the leading economic activities that can be developed in increasing the economic potential in Jember District. Analyzer used in this research include analysis of Shift-Share, Location Quotient (LQ), and Growth Ratio Model (MRP). From the research result, it can be seen that: (1) shift-share analysis shows Jember Regency economy during 2010-2015 period increased by Rp2,412.3 billion. The improvement of economic performance in Jember Regency can be seen from positive sector of agriculture sector, forestry and fishery; (2) Based on the analysis of Location Quotient (LQ) sector and the leading sub-sector in Jember Regency there is 1 sector and 1 sub-sector having average LQ> 1 or sector and subsector of the (potential) ie agriculture, farming, and plantation sub-sector; (3) Growth Ratio Model (MRP) analysis shows that the dominant sectors of growth and large contribution include estate crop sub-sector, agriculture and hunting services sub sector, forestry and logging sector, and fishery sector; (4) weighted results based on Shift-Share, Location Quotient (LQ) and Growth Ratio (MRP) analysis were obtained by the highest ranking sub-category of the most potential weighted crops sub-sector.